Proyecto de factibilidad para la creación de una empresa productora y comercializadora de mesas de billa y billar en la ciudad de Quito. - Proaño Mena, Roberto Napoleón (2012)
The market study aims to provide a deeper understanding of the current conditions of demand and supply and billiard tables billa in the city of Quito. Information collected will perform later in the projection of both the applicants and the number of tables that manufacturers put on the market for consumption, concluding on the existence of unmet demand, it will serve as a guide to define productive capacity that the factory must have to satisfy consumers. Estimated the number of people who will demand existing pool tables or billa, the study focused on identifying the structure of the market, the conditions for marketing and distribution channels used to sell the product